2011
DOI: 10.1080/15459624.2011.583488
|View full text |Cite
|
Sign up to set email alerts
|

Development of Solvent Exposure Index for Construction Painters

Abstract: This article describes methodological approaches for reconstructing long-term occupational exposure to organic solvents among construction painters. A detailed exposure questionnaire was administered to 125 painters to develop a job exposure matrix (JEM). The questionnaire inquired about painting activities with solvent-based paints and use of protection equipment for the previous 25 years in 5-year intervals. Current and historical distributions of solvent air concentrations were assessed for the same time pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 24 publications
1
10
1
Order By: Relevance
“…Estimates of exposure were then modified by current and historical solvent air concentrations from field measurements and an extensive search of industrial, governmental, and academic databases. (59) In addition, our solvent exposure index predicted reduced neural activation (fMRI) during a working memory task, thereby substantiating the predictive validity of our exposure assessment method against a biological measurement of cognitive performance. (39) Nevertheless, any exposure index based on historical recall is subject to inaccuracies and recall bias that could result in random misclassification.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…Estimates of exposure were then modified by current and historical solvent air concentrations from field measurements and an extensive search of industrial, governmental, and academic databases. (59) In addition, our solvent exposure index predicted reduced neural activation (fMRI) during a working memory task, thereby substantiating the predictive validity of our exposure assessment method against a biological measurement of cognitive performance. (39) Nevertheless, any exposure index based on historical recall is subject to inaccuracies and recall bias that could result in random misclassification.…”
Section: Discussionsupporting
confidence: 59%
“…Typical workplace air concentrations of solvents and emission of solvents from paint products have steadily declined over the past 20 years. (59) Although our study documented some associations between the solvent exposure index and individual measures of behavioral performance, these associations reflected relatively small differences and were not seen across all measures within a domain. In addition, many solvent exposed participants reported using protective equipment when at most risk for high exposure such as during spray painting activities.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…While estimating the past exposure levels, we should consider the painting method (spray, roller, brush), painting time, and use of respiratory protective equipment. Wang et al [11] reported that the most influential environmental factors affecting TVOC concentrations were the painting method (spray, roller, brush) and painting time. In addition, spray-type painting while wearing respiratory protective equipment generates higher TVOC concentrations than roller- and brush-type painting even without wearing respiratory protective equipment.…”
Section: Discussionmentioning
confidence: 99%